Nujno dedovanje na prepihu časa - Žnidaršič Skubic, Viktorija (Pravni letopis, 2025)
The author discusses the current inheritance law issues of compulsory inheritance from the perspective of national and comparative law, and especially in light of the need for new regulations in this area in the Republic of Slovenia. Compulsory inheritance represents the great est restriction on the testator’s freedom to make a will, which is based on the autonomy of the individual as one of the most highly protected goods in the age of liberal individualism. Nevertheless, almost everywhere in the world (with the exception of common law countries), there is a certain type of mandatory participation of the testator’s closest relatives in a certain part of his or her estate. The question arises as to whether such a regulation is still appropriate or whether the requirement to protect family solidarity in this way goes too far. Individual countries respond differently to modern demographic and other trends that dictate changes in inheritance law. This article presents various aspects highlighted by comparative law and theory, which argue both for the existence and the abolition of the institution, or its subordination to the demonstrated needs of the forced heirs. The author presents her views on the issue of amending this area of Slovenian law.
Keywords: compulsory inheritance; compulsory portion; Dedovanje in nasledstvo; dolžni delež; forced heirs; forced share; nujni dediči; nujni delež; nujno dedovanje; sistemi nujnega dedovanja; systems of forced succession